Hubungan antara Rentang Waktu Terjadinya Serangan Hingga Tiba di RSUD Dr. Moewardi dengan Prognosis Stroke Iskemik - Gia Noor Pratami; Suroto .; Diah Kurnia Mirawati (Nexus Kedokteran Klinik, 2012)
Background: Stroke is the third leading cause of death in the world. The awareness of early signs and symptoms of stroke and referral to hospital efforts should be made because the successful treatment of stroke is determined by the speed of action in the acute phase (therapeutic window). In ischemic stroke, restoration or improvement of perfusion to the ischemic area is a therapy key. This study is aimed to determine the relationship between time range from stroke attack until arrive at the Dr. Moewardi hospital with ischemic stroke prognosis. Methods: This study was observational cohort analytic approach. A total of 48 subjects were selected by purposive sampling, they were ischemic stroke patients in the room Orchid II Dr. Moewardi Hospital. Data was collected by direct interview and examination of the patient by using NIHSS score. Data was analyzed by using multiple logistic regression models and processed with Statistical Product and Service Solutions (SPSS) for Windows 17.00. Results: Multiple logistic regression showed the results OR = 1.89; CI 95% 0.395 9.035; and p=0.425. This result has controlled the confounding variables of age, blood pressure, blood sugar levels, and colesterol levels. Patient who arrived at the Dr. Moewardi hospital >24 hours after the stroke attack increases the risk of poor prognosis 1.890 times than that arrived at the hospital <6 hours and 6-24 hours. Conclusions: There is a moderate correlation between the time range from stroke attack until arrive at the Dr. Moewardi hospital with ischemic stroke prognosis, although in this study the relationship was not statistically significant. Keywords: time range, attack, Dr. Moewardi hospital, prognosis, ischemic stroke